Regulation Of Cryptocurrency In Indonesia: An Integrative Approach Between Positive Law And Islamic Law For Risk Mitigation - Ahmad Azim Aufaq; Bakhrul Huda (Borneo Islamic Finance and Economics Journal, 2025)
Cryptocurrency in Indonesia faces complex regulatory challenges, given its legal status as a digital asset but its illegality as a means of payment. This legal uncertainty is exacerbated by the incompatibility of cryptocurrency practices with Sharia principles, particularly due to elements of gharar (uncertainty) and maysir (gambling), which are prohibited in Islamic law. This study aims to examine cryptocurrency regulation through an approach that integrates positive law and Islamic law, while formulating a risk mitigation model to ensure compliance with both legal systems. Employing normative legal methods and a juridical-philosophical approach, this research identifies the existing legal dualism and proposes the "Hybrid Regulatory Compliance" model, which integrates the legal certainty principles of positive law with the maslahah (public interest) of Islamic law. This approach is expected to create a more ethical and stable cryptocurrency ecosystem, thereby enhancing the trust of Muslim investors in Indonesia. The developed model also offers practical solutions for regulators and stakeholders to harmonize cryptocurrency regulations with Sharia principles comprehensively.